Suppressing surface segregation by introducing lanthanides to enhance high-temperature oxygen evolution reaction activity and durability - Jingwei Li; Zichao Wu; Yuxiang Shen; Yuefeng Song; Houfu Lv; Xiaomin Zhang; Guoxiong Wang (JPhys Energy)
Ba _0.5 Sr _0.5 Co _0.8 Fe _0.2 O _3− _δ (BSCF) is a conventional anode material for solid oxide electrolysis cells (SOECs) to catalyze oxygen evolution reactions (OERs). However, the inferior chemical stability of BSCF results in severe surface segregation and performance degradation under high temperatures. A critical challenge lies in alleviating surface segregation and preserving the high OER performance of BSCF anodes. Herein, lanthanides are introduced to substitute the Ba in BSCF, labeled as Ln _0.5 Sr _0.5 Co _0.8 Fe _0.2 O _3− _δ (LnSCF, Ln = La, Pr, Nd, Sm), to regulate its stability and performance. The introduction of La and Pr effectively enhances stability, suppresses surface segregation and maintains high OER activity. Continuous lattice oxygen loss and Co ion oxidation of LnSCF are demonstrated upon annealing in oxidizing atmosphere; thus, we propose that surface segregation is a self-regulation mechanism of perovskite lattice to tolerant oxidizing atmosphere. Perovskite oxides maintain structurally stable via decreasing A-site valence state and forming surface segregation. SOECs with La _0.5 Sr _0.5 Co _0.8 Fe _0.2 O _3− _δ anodes deliver an optimal current density of 1.69 A cm ^−2 at 1.6 V and stability for CO _2 electrolysis at 800 °C, shedding light on designing advanced catalysts for high-temperature OER.